Planning support system for sustainable development in Malaysia: a case analysis of Selangor State, Malaysia - Abdullah, Muhammad Faris; Abdullah, Alias; Abdul Samad, Dazilah; Shahbudin, Muhamad Nur Azraei; Klosterman, Richard (2006)
Sustainable development is the kind of development every planner is striving to achieve. The term ‘sustainable development’ has been wide ranging. The World Commission on Environment and Development (WCED) in its report, "Our Common Future", defined sustainable development as "development that meets the needs of the present without compromising the ability of future generations to meet their own needs". In Malaysia, development plans are being prepared as part of the effort to achieve sustainable development. There are three levels of plan preparation adopted in Malaysia, i.e. National Physical Plan, State Structure Plan and District Local Plan. Policies are formulated and land use zoning is determined in these development plans but land allocation, demand and supply analysis, land budgeting, etc is lacking. There is no indication of areas suitable for development. The What If? Planning Support System gives chances to analyse and project land location and allocation for future development. It is a GIS-based, policy-oriented planning support system that uses increasingly available geographic information system (GIS) data to support community-based processes of collaborative planning and collective decision making. Thus, this study intends to show its application in the state of Selangor and to compare the results to that of the Selangor State Structure Plan.